Pemecahan Masalah Materi Persamaan Linear Satu Variabel dengan Scaffolding di Kelas VII Ali Bin Abi Thalib MTsN Pucanglaban Tulungagung - Ni’mah, Siti Fatkun; Sutopo, Sutopo (Jurnal Tadris Matematika, 2018)
This research is based on the problems faced by students in solving math problems. Where these problems can hinder the success of students in the learning process. Therefore, researchers take a scaffolding step to overcome the difficulties faced by students in solving the problem of linear equations of one variable. The purpose of this research is to determine the type of the difficulties faced by students in problem solving linear equations one variable in class VII State Islamic Junior High School Pucanglaban and to describe the process of scaffolding students in problem solving linear equations one variable in class VII State Islamic Junior High School Pucanglaban. This study uses a qualitative approach, while based on the discussion techniques included in descriptive research. Methods of data collection using: observation, test, in-depth interviews, and notes field, and documentation as supporting data. Data analysis technique used is qualitative data analysis with steps: data reduction, data presentation and conclusion. The conclusion of this study were: (1) Difficulties faced by students in solving mathematical problems one variable linear equation materials are: (a) in understanding the problem, (b) in making a mathematical model, (c) to operate, and d) in drawing conclusions. (2) Provision of appropriate scaffolding to overcome the difficulties that students face, is as follows: (a) to overcome the difficulties students in understanding the problem, appropriate scaffolding is explaining, reviewing and restructuring. (b) to overcome student difficulties in making mathematical models, appropriate scaffolding is reviewing, and restructuring. (c) to overcome difficulties in operating, appropriate scaffolding is restructuring. (d) to overcome difficulties in drawing conclusions, appropriate scaffolding is developing conceptual thinking.